El mesianismo polaco como respuesta al problema de la identidad nacional en la Polonia del siglo XIX - Fernando, PRESA GONZÁLEZ (Revista de Filología Románica, 2002)
The Polish Romanticism has a deep foundation mystic that takes it to the apology of the sacrifice like redemption in front of the historical reality and that it ends in the mesianism. This belief took the environment of the historical reality the consequences of the death and Christ’s resurrection, as well as of the metaphysical act of the humanity’s redemption by means of its sacrifice. In the history of Poland he repeats the same symbolic biography: the innocent victim, the martyrdom, the death and the redemption. Christ in the cross is the analogy of a Poland murdered by the allotments. Their martyrdom is the successive risings, frustated and full with victims. To this it owes himself the sacral and the cult romantic Pole to the suffering and the martydrom. The sacrifice didn’t only guarantee the redemption but it also confirmed the fact that the Polis nation is the elect to redeem to the rst of the nations.